Three-dimensional femtosecond laser inscription of type a-based high-efficiency first-order waveguide Bragg gratings - Laberdesque, Romain; Loi, Laura; Guérineau, Théo; Khalil, Alain Abou; Danto, Sylvain; Cardinal, Thierry; Canioni, Lionel; Petit, Yannick (Advanced Optical Technologies, 2023)
A novel type of waveguide Bragg grating (WBG) is demonstrated based on femtosecond laser-induced Type A refractive index modifications, namely based of the photochemistry of silver species in a specialty ortho-phosphate glass matrix. First-order WBGs are reported in the near-infrared and down to 736 nm in the visible. Relative transmission measurements with a 500 µm long WBGs lead to narrow-bandwidth attenuations (sub-nm spectral FWHM) from 2.29 dB to 6.25 dB for periods from 240 nm to 280 nm, respectively. The corresponding estimated backward coupling coefficients show high values from 1.66 mm-1 up to 2.69 mm-1. Additionally, we report on a true 3D helix-shaped WBG that shows an even stronger relative attenuation of 10.3 dB for a 500 µm long WBG, equivalently corresponding to a backward coupling coefficient of 3.7 mm-1. These novel results pave the way for new silver-based laser-inscribed integrated photonic devices, among which the combination of Bragg gratings to form active/passive optical resonators, but also the direct inscription of WBG at the glass interface for enhanced sensing applications.